Jurisprudence : theory and context - Bix, Brian (2015)
This title explores and integrates models of practice and negotiation, examines strategies and provides precedents.Assists practitioners, policy makers and the judiciary in addressing the issues affecting practice.
Overview, purpose and methodology -- Legal theory : general jurisprudence and conceptual anlysis -- H.L.A. Hart and legal positivism -- Hans Kelsen's pure theory of law -- Natural law theory and John Finnis -- Understanding Lon Fuller -- Ronald Dworkin's interpretive approach -- Justice -- Punishment -- Rights and rights talk -- Will and reason -- Authority, finality and mistake -- Common law reasoning and precedent -- Statutory interpretation and legislative intentions -- Legal enforcement of morality -- The obligation to obey the law -- American legal realism -- Economic analysis of law -- Modern critical perspectives -- Law and literature -- Philosophial foundations of the common law -- Other approaches.
Includes bibliographical references (pages 293-331) and index.
Keywords: Jurisprudence; Law -- Philosophy; Rechtsphilosophie; Rechtstheorie; Jurisprudence; Law -- Philosophy